Platinum‐Decorated Ultrafine Pd Nanoparticles Monodispersed on Pristine Graphene with Enhanced Electrocatalytic Performance. Issue 2 (29th October 2015) - Wang, Haining; Lu, Shanfu; Zhang, Yiwen; Lan, Fei; Shang, Jiaxiang; Xiang, Yan
Abstract: Ultrafine and monodispersed Pd particles with a size of approximately 1.7 nm on pristine graphene are decorated with a low loading of Pt through a spontaneous deposition method. The electrocatalytic activity and poisoning species tolerance toward formic acid oxidation is improved after Pt decoration. Theoretical calculations reveal more continuous d‐states of the partial density of states and a downshift of the d‐band center in the Pt‐decorated Pd catalysts, which result in better electrocatalytic performance. Abstract : Formic acid electro‐oxidation : Ultrafine and monodispersed Pd nanoparticles on graphene sheets are decorated with a low Pt loading (see figure). The decorated particles exhibit enhanced electrocatalytic activity and stability for the formic acid oxidation reaction.